Pengaruh Penerapan E-Faktur Dan E-SPT Pajak Pertambahan Nilai (PPN) Terhadap Kepatuhan Pengusaha Kena Pajak Yang Terdaftar Di KPP Pratama Jayapura - Liing, Yose Maria Fabiola Da; Allolayuk, Paulus K.; Seralurin, Yohanes C (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
This research aims to provide empirical evidence of the influence of implementing e-invoices and e-SPT Value Added Tax (VAT) on the compliance of taxable entrepreneurs registered at KPP Pratama Jayapura. Data collection in this research used a questionnaire distributed directly to Taxable Entrepreneurs (PKP) registered at KPP Pratama Jayapura. The sampling technique used in this research was purposive sampling with a total of 73 respondents taken. The data analysis method used in this research is a survey method by giving a number of questionnaires to taxable entrepreneurs at KPP Pratama Jayapura which are then analyzed with the help of SPSS 25. Based on the tests carried out, the research results show that, partially the implementation of E-invoicing has a significant effect on the compliance of taxable entrepreneurs, and the E-SPT Value Added Tax (VAT) has a significant effect on the compliance of taxable entrepreneurs registered at KPP Pratama Jayapura while simultaneously (together) the implementation of E-invoices and E-SPT value added tax (VAT) has a significant effect on the compliance of taxable entrepreneurs registered with KPP Pratama Jayapura.